Employer Requirements to Work during Emergency Responses: Key Ethics Considerations. Issue 1 (2017) - Rutkow, Lainie; Taylor, Holly A.; Powell, Tia
Abstract : Local health departments and their employees are at the forefront of emergency preparedness and response. Yet, recent studies have found that some local public health workers are unwilling to report to work in a variety of disaster scenarios. This can greatly compromise a response, as many local health departments need "all hands on deck" to effectively meet increased demands. To address these concerns, local health departments have employed varied policy strategies to ensure that employees do report to work. After describing different approaches taken by local health departments throughout the United States, we briefly identify and explore key ethics considerations that arise for local health departments when employees are required to report to work for emergency responses. We then discuss how these ethics considerations may inform local health department practices intended to promote a robust emergency response.